PENGARUH PERTUMBUHAN EKONOMI DAN BELANJA MODAL TERHADAP INDEKS PEMBANGUNAN MANUSIA (IPM) DALAM PERSPEKTIF ISLAM - Anggatia Ariza (Al-Maslahah : Jurnal Ilmu Syariah, 2016)
Prosperity is the ultimate goal of every nation or region that can be achieved through economic development. One of its indicators is Human Development Index (HDI) of the region. This research is aimed at identifying the effect of economic development and capital expenditure towards HDI. The data used in the research were panel data gained from fourteen cities/regencies in West Kalimantan in 2008 to 2012. The data were analysed by means of fixed effect method. The findings show that economic development and capital expenditure positively and significantly affect human development index.